Shifting microbial communities in acidified seawaters: insights from polychaetes living in the CO2 vent of Ischia, Italy - ARNOLDI, Irene; CARRARETTO, Davide; MUNARI, Marco; NANNINI, Matteo; GAMBI, Maria Cristina; CANNAVACCIUOLO, Antonio; DELLA TORRE, Camilla; GABRIELI, Paolo (Integrative Zoology, 2024)
Oceans' absorption of human-related CO2 emissions leads to a process called ocean acidification (OA), consisting of the decrease of the seawater pH with negative consequences for many marine organisms. In this study, we investigate the microbial community of two species of polychaetes found in naturally acidified CO2 vents: the nereid Platynereis massiliensis complex and the syllid Syllis prolifera. Animals were collected in the CO2 vents of Castello Aragonese (Gulf of Naples, Ischia, Italy) in three zones at decreasing pH. For the analysis of the microbiome, the V3-V4 hypervariable region of the 16S ribosomal RNA gene of 40 worm samples was sequenced on an Illumina MiSeq platform. No difference in the microbial alpha diversity of both species was highlighted. On the contrary, the microbial composition of worms collected in the site at normal pH was different from that of the individuals obtained from the sites at lower pH. This effect was evident also in samples from the site with a slight, but relevant, degree of acidification. Amplicon sequence variants showing a significant variation among the groups of samples collected from different pH zones were reported for both polychaetes, but no common trend of variation was observed. The present study deepens our knowledge about the composition of polychaete microbiome in marine naturally acidified sites. Our results stress the importance of future investigations about the connection between the variation of environmental and polychaete microbial communities induced by OA and about the effect of these variations on polychaete key biological and ecological traits.